Review: The spirit moves West: Korean missionaries in America by Rebecca Y. Kim - TSE, Justin Kh (Institutional Knowledge at Singapore Management University, 2016)
The Spirit Moves West is Pepperdine University sociologist Rebecca Kim's study of missionaries from the Republic of Korea (ROK) to the United States. Kim tells her story through the case study of one Korean missionary organization, University Bible Fellowship (UBF), which was launched in the wake of ROK student unrest in 1961 by American missionary Sarah Barry and Korean pastor Samuel Chang-Woo Lee in Kwangju. Facilitated by Kim's own familial connections at UBF, this sociological account of the organization focuses on its work on American university campuses, an effort launched in 1970 as part of UBF's global campaign to place missionaries in academic institutions in over eighty countries.